Perlindungan Hukum Terhadap Pekerja Outsourcing (Studi Pada PT. Arina Tama Persada) - Pardede, Fransthahi Hamonangan; Nurhayati, Siti; Aspan, Henry (Jurnal Christian Humaniora, 2025)
Outsourcing workers in Indonesia must be protected to achieve welfare. Outsourcing workers at the Animal, Fish, and Plant Quarantine Center of North Sumatra placed through the company PT Arina Tama Persada for the status of working as a cleaning service have several obstacles in obtaining their rights that are not fulfilled. The main rights of workers that are not fulfilled are regarding work contracts/agreements. The contract is only made verbally between PT Arina Tama Persada and outsourcing workers. As regulated in Article 18 of Law No. 35 of 2021, it is clearly stated that the employment relationship between the outsourcing company and the workers/laborers employed is based on the PKWT and PKWTT which must be made in writing. When workers ask for an employment agreement to PT Arina Tama Persada as the work provider company, they always do not respond and state that the contract is made verbally. This study uses an empirical legal method with a field approach through interviews and observations, as well as literature studies. The results of the study show that the management of PT Arina Tama Persada as the work provider company who is not willing to be interviewed is clear evidence of the company's lack of openness in providing the rights of outsourcing workers at the North Sumatra Animal, Fish and Plant Quarantine Center with the status of a cleaning service. The management of PT Arina Tama Persada, verbally but not willing to be interviewed, admitted that there were many shortcomings in the fulfillment of workers' rights. PT Arina Tama Persada was the winner of a government auction to employ outsourced workers at the Animal, Fish, and Plant Quarantine Center of North Sumatra. Because the work deals with the interests of outsourced workers at the Animal, Fish, and Plant Quarantine Center of North Sumatra with the status of cleaning service, then PT Arina Tama Persada as the provider of outsourced workers should be transparent.